1992
DOI: 10.1164/ajrccm/145.6.1384
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Heart Rate Response to Hypoxia in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Effects of acute, progressive isocapnic hypoxia on heart rate (HR) and ventilation were determined in 31 patients with chronic obstructive pulmonary disease (COPD) and in 24 normal control subjects. There was an inverse linear relationship between heart rate and SaO2 in each subject. The slope factor (delta HR/delta SaO2) obtained from the regression line was significantly higher in the patients with COPD than in the normal control subjects (0.888 +/- 0.309 SD beats/min/% fall in SaO2 versus 0.693 +/- 0.287; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…This tachycardia may be due to multiple causes including hypoxemia or medications. Our patients all presented with a marked hypoxemia and COPD patients are known to show a more pronounced reaction to low blood oxygen content (15). Medications given to the COPD patients included ␤ 2 -agonist, theophylline, or atropine, all potentially responsible for tachycardia.…”
Section: Discussionmentioning
confidence: 98%
“…This tachycardia may be due to multiple causes including hypoxemia or medications. Our patients all presented with a marked hypoxemia and COPD patients are known to show a more pronounced reaction to low blood oxygen content (15). Medications given to the COPD patients included ␤ 2 -agonist, theophylline, or atropine, all potentially responsible for tachycardia.…”
Section: Discussionmentioning
confidence: 98%
“…Studies showed a relationship between higher resting heart rate and low levels of PaO 2 . The presence of hypoxemia increased resting heart rate 49% per ten beats per minute 35,36. In accordance with the literature, the hypoxemic patients in our study also exhibited elevated heart rate responses during exercise testing.…”
Section: Discussionmentioning
confidence: 99%
“…(1996) noted an inverse correlation between FEV 1·0 and plasma noradrenaline concentration. Furthermore, obstruction of the bronchi and hypoxaemia are known to increase sympathetic activity (Miyamoto et al. 1992; Heindl et al.…”
Section: Discussionmentioning
confidence: 99%